2004
DOI: 10.1093/hmg/ddi036
|View full text |Cite
|
Sign up to set email alerts
|

Myosin XVa and whirlin, two deafness gene products required for hair bundle growth, are located at the stereocilia tips and interact directly

Abstract: Defects in myosin XVa and the PDZ domain-containing protein, whirlin, underlie deafness in humans and mice. Hair bundles of mutant mice defective for either protein have abnormally short stereocilia. Here, we show that whirlin, like myosin XVa, is present at the very tip of each stereocilium in the developing and mature hair bundles of the cochlear and vestibular system. We found that myosin XVa SH3-MyTH4 region binds to the short isoform of whirlin (PR-PDZ3) that can rescue the stereocilia growth defect in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
187
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(194 citation statements)
references
References 24 publications
7
187
0
Order By: Relevance
“…However, recent work has established that whirlin, a PSD-95͞SAP90 Discs-large ZO-1 homologous (PDZ) protein, localizes to the stereocilia tips and, by virtue of mutations in the whirlin gene, has been shown to play an important role in stereocilia development (7). Myosin XVa interacts with whirlin and is responsible for localizing whirlin at the stereocilia tip (8,9). We have recently shown that whirlin expression is dynamic during stereocilia growth, further underlining its key role in stereocilia development (10).…”
mentioning
confidence: 99%
“…However, recent work has established that whirlin, a PSD-95͞SAP90 Discs-large ZO-1 homologous (PDZ) protein, localizes to the stereocilia tips and, by virtue of mutations in the whirlin gene, has been shown to play an important role in stereocilia development (7). Myosin XVa interacts with whirlin and is responsible for localizing whirlin at the stereocilia tip (8,9). We have recently shown that whirlin expression is dynamic during stereocilia growth, further underlining its key role in stereocilia development (10).…”
mentioning
confidence: 99%
“…Are there other cargos transported by myosin XV? Delprat et al (2005) proposed that whirlin interacts with a transmembrane protein, NGL-1, isolated from a P2-P6 mouse inner ear cDNA library. In light of similarities between the unconventional myosins XV and VIIa, the PDZ domain proteins whirlin and harmonin, and the transmembrane proteins NGL-1 and cadherin 23, these proteins may form two similar complexes required for stereocilia morphogenesis.…”
Section: Genes With Genotype Effectsmentioning
confidence: 99%
“…Myosin XV is normally located at the tips of stereocilia and within the actin-rich cuticular plate that anchors the bases of the stereocilia (Liang et al 1999;Belyantseva et al 2003). Myosin XV was recently shown to be essential in transporting whirlin to the tips of stereocilia (Belyantseva et al 2005;Delprat et al 2005;Kikkawa et al 2005). Defective myosin XV proteins in sh2 mice disrupt relevant structural interactions and/or biochemical pathways associated with this transport system and lead to stereocilia malformation.…”
Section: Introductionmentioning
confidence: 99%
“…Class III myosins shape the auditory hair bundles by limiting microvilli and stereocilia growth myosin XVa, is located at the tips of the stereocilia and forms a complex with the PDZ domain-containing protein whirlin and the actin regulatory protein Eps8, whose disruption causes stereocilia to be abnormally short at postnatal stages (Probst et al, 1998;Delprat et al, 2005;Manor et al, 2011). Myosin VIIa, defects of which cause Usher syndrome type I (USH1; Weil et al, 1995), forms a complex with other USH1 proteins harmonin,and Sans), which is required for the cohesiveness of the growing hair bundle (Petit and Richardson, 2009).…”
Section: Introductionmentioning
confidence: 99%